An investigation of spatial database in Klang valley and Kuala Lumpur / Nur Aziza Romai Nar - Romai Nar, Nur Aziza (2005)
Spatial database is simply a database that contains spatial information. This research focuses in spatial database awareness in the company around Klang Valley and Kuala Lumpur. Other than that this research will study in which application or field the spatial database is currently used or undergoing research. We also define how spatial database is being implemented or the methodology to develop spatial database. A study information scent is taken from the methodology that being used such as interviewing and distributing questionnaire to the companies. From this study, we find out that the Geographic Information System (GIS) provider in Malaysia is the one that has been use spatial database extensive. The report of the findings is divided into several chapters and subchapters to explain each of the result more clearly and in organized manner.